Dinamika Pertumbuhan Penduduk dan Tantangan Sosial di Tengah Perkembangan Industri Kabupaten Serang - Wahidatul Asna; Akrom A (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
Industrial development in Serang Regency has been accompanied by population growth and the emergence of various social challenges within the community. This study aims to analyze population growth dynamics and social challenges amid industrial development in Serang Regency. The research employed a descriptive qualitative approach using a literature study method. The data consisted of secondary sources obtained from publications of Statistics Indonesia (BPS), scientific journals, articles, and other relevant documents. Data collection was conducted through documentation techniques, while data analysis applied descriptive qualitative analysis through data reduction, data presentation, and conclusion drawing. The results indicate that the population of Serang Regency increased from 1,622,630 people in 2020 to 1,701,803 people in 2024, with a population growth rate of 1.42%. The expansion of the industrial sector, which absorbs a large number of workers, has been accompanied by increasing population mobility toward industrial areas, particularly Cikande District. This condition reflects a concentration of population in areas with more developed economic activities. In addition, the increasing population in industrial areas is accompanied by various social challenges, including greater demand for infrastructure and public services, competition for employment opportunities, and changes in patterns of social interaction. Therefore, development planning that considers demographic and social aspects is necessary to ensure that industrial development remains aligned with community welfare.